STRATEGIC HUMAN RESOURCE MANAGEMENT (SHRM) DI KEMENPAN-RB REPUBLIK INDONESIA - Fauziah, Nike Mutiara; Prasetyo, Andri Wahyu (Universitas Widya Mataram, 2020)
This study focuses on change management towards Strategic Human Resource Management (SHRM) in the Ministry of Administrative and Bureaucratic Reform of the Republic of Indonesia (KemenPAN-RB). Considering on idea of change HR management towards SHRM which could not be implemented, and various issues related to human resource management in KemenPAN-RB. This study uses a qualitative method with postpositivis approach. The object of this research is the Ministry of Administrative and Bureaucratic Reform of The Republic of Indonesia as a unit of analysis. The data analysis technique in this research was conducted by triangulation of source. The results show the human resource management in KemenPAN-RB still Partial Human Resource Management in managing human resources, because of human resource management are still not integrated which causes various problems in aspects of competency management, recruitment and selection, human resource development, performance appraisal, career management and total reward system. The idea of change towards SHRM could not be implemented due to various influence factors. There are some factors influenced implementing of SHRM according to the result of author analysis taken from various interviews has been conducted those are Mindset factor, Organizational, Leadership, Sharing Knowledge, Infrastructure and HR Competency.